2016
DOI: 10.1002/cbic.201600229
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversification of Lyngbyatoxin A by Host‐Dependent Heterologous Expression of the tleABC Biosynthetic Gene Cluster

Abstract: Natural products have enormous structural diversity, yet little is known about how such diversity is achieved in nature. Here we report the structural diversification of a cyanotoxin—lyngbyatoxin A—and its biosynthetic intermediates by heterologous expression of the Streptomyces‐derived tleABC biosynthetic gene cluster in three different Streptomyces hosts: S. lividans, S. albus, and S. avermitilis. Notably, the isolated lyngbyatoxin derivatives, including four new natural products, were biosynthesized by cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The limited host range of genetic elements like conjugal plasmids or pathogenicity islands as well as codon usage, the availability of metabolic precursors, or differences in transcription and regulation place restrictions on horizontal gene cluster transfer making the spread of natural product biosynthetic pathways more common among closely related organisms . However, horizontal gene transfers are necessary to explain the production of identical secondary metabolites by microbes belonging to different phyla, for example, the lyngbyatoxin biosynthetic pathway is found in both the actinobacteria and cyanobacteria phyla , while the macrolide scytophycin is found in both the proteobacteria and cyanobacteria phyla . The same natural product can also be shared between organisms from different domains, for example, the UV‐sunscreen mycosporine is produced by a range of photosynthetic algae and bacteria , the beta‐lactam antibiotic penicillins and cephalosporins are produced by fungi and bacteria , and potent neurotoxic saxitoxins are produced by both cyanobacteria and dinoflagellates.…”
Section: Horizontal Gene Transfer Facilitates the Distribution Of Natmentioning
confidence: 99%
“…The limited host range of genetic elements like conjugal plasmids or pathogenicity islands as well as codon usage, the availability of metabolic precursors, or differences in transcription and regulation place restrictions on horizontal gene cluster transfer making the spread of natural product biosynthetic pathways more common among closely related organisms . However, horizontal gene transfers are necessary to explain the production of identical secondary metabolites by microbes belonging to different phyla, for example, the lyngbyatoxin biosynthetic pathway is found in both the actinobacteria and cyanobacteria phyla , while the macrolide scytophycin is found in both the proteobacteria and cyanobacteria phyla . The same natural product can also be shared between organisms from different domains, for example, the UV‐sunscreen mycosporine is produced by a range of photosynthetic algae and bacteria , the beta‐lactam antibiotic penicillins and cephalosporins are produced by fungi and bacteria , and potent neurotoxic saxitoxins are produced by both cyanobacteria and dinoflagellates.…”
Section: Horizontal Gene Transfer Facilitates the Distribution Of Natmentioning
confidence: 99%
“…Expression of tleABC in three different hosts S. albus G153, S. lividans TK21 and S. avermitilis SUKA22 revealed unexpected host-pathway interactions. Although two intermediates valindolmycin and indolactam V and the final product lyngbyatoxin A were detected in all hosts, new analogues that are absent in both native producer and hosts were produced (Zhang et al, 2016a). Interestingly, these analogues were produced in a host-specific manner; different host preferably recognizes different compounds in the lyngbyatoxin pathway.…”
Section: Streptomyces Lividans As a Heterologous Hostmentioning
confidence: 99%
“…For example, S. lividans used indolactam V to generate analogues; while S. albus and S. avermitilis interacted with the early intermediate valindolmycin and the final product lyngbyatoxin A, respectively. The host specific generation of lyngbyatoxin A analogues was summarized in Figure 4 (Zhang et al, 2016a). …”
Section: Streptomyces Lividans As a Heterologous Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…One key issue that is difficult to address, especially for gene clusters for which the real molecular product is unknown beforehand, is that of cross-talk between the heterologously expressed pathway and the native pathways. A recent study by Zhang et al showed that heterologous expression of the lyngbyatoxin gene cluster in three different streptomycete hosts lead to the generation of different natural product derivatives [78]. Because small variations in chemical structure can have a major impact on biological activity, expression studies in multiple hosts (or multiple versions of the same hosts with different native BGCs knocked out using, e.g.…”
Section: Grapementioning
confidence: 99%